Committed to implementing CCU? A comparison of the policy mix in the US and the EU - Thielges, Sonja; Olfe-Kräutlein, Barbara; Rees, Alexander; Jahn, Joschka; Sick, Volker; Quitzow, Rainer (Frontiers in Climate, 2022)
Carbon capture and utilization (CCU) technologies aim to use carbon dioxide (CO2), either captured from industrial point sources or from the atmosphere, instead of fossil carbon in the production of a variety of valuable goods. CCU has the potential to contribute to emission reductions and to lower raw material consumption as well to foster transitional processes towards a circular economy. To enable societies to take full advantage of this potential, policy support is needed in overcoming current barriers and fostering CCU implementation as a feasible option for the industry. Based on a literature and online investigation, this paper identifies and compares the current policy mixes for CCU in the US and the EU, focusing on policy strategies and existing and proposed policy instruments. The analysis shows that US strategy documents, with very few exceptions, do not mention CCU specifically in the context of the country’s 2030 or 2050 climate targets. In the EU, in contrast, the future role of CCU is clearly linked to achieving climate-neutrality by 2050. The main policy instruments to incentivize the implementation of CCU in the US are tax credits (45Q). Moreover, funding exists for research and development efforts. In the EU, many reform proposals are currently underway that could benefit CCU technologies. At present, policy support, for instance through the Renewable Energy Directive, mainly aims at renewable fuels of non-biological origin while in other areas CCU support remains at odds with principles such as “energy efficiency first”. The EU does, however, have a broad range of funding opportunities available for research, development and demonstration projects. Based on an assessment scheme borrowed from Rogge and Reichardt (2016), the paper uses the cross-regional comparison of policy mixes to formulate policy recommendations to improve policy mixes for CCU. A clearer strategic commitment to CCU, its incorporation into green public procurement guidelines, incorporating CCU across different funding schemes for sustainable energy transition, and ambitious new targets for renewable electricity and green hydrogen, for instance, could help develop the policy mixes further to provide a supportive framework for CCU.